Epstein’s ’Metabole’ and Kedrov’s ’Metametaphor’ as a poetic-artistic revision of metaphor: about two key terms of metarealism - Fedorushkov, Edyta (Acta Universitatis Lodziensis. Folia Litteraria Rossica, 2016)
The aim of the paper is to describe two key terms of metarealism (a literary movement in the Russian poetry of the 1980s), namely ‘metabole’ and ‘metametaphor’. These concepts reevaluate the concept of metaphor and at the same time become the essential poetic-artistic idea of metarealism. The paper outlines their mechanism of action, on basis of the manifestos written by the authors of the terms – Mikhail Epstein and Konstantin Kedrov respectively. The analysis of the multilevel functioning of ‘metabole’ and ‘metametaphor’ in a poem allows the author to reach the conclusion that the two figures form a new type of worldview, which revises the idea of primal oneness and inseparableness of all things.